2000
DOI: 10.1023/a:1005521014919
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Treatment of psychosocial/emotional distress as a strategy for diminishing chest pain in such patients remains entirely unutilized in standard care. Sixty-three patients with known or suspected CAD were entered in an aggressive lifestyle modification program. Patients completed the Symptom Checklist 90-Revised (SCL90R) at the diagnostic interview session, at 3 and at 12 months. Statistically significant drops were observed on multiple scales of the SCL90R at both 3 and 12 months. An item from the SCL90R was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In several studies, treatment of distress has been found to reduce utilization and costs [21, 7577]. Aggressive, angina-targeted clinical trials that also evaluate impact on utilization, and trials using modern psychopharmacological agents, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, treatment of distress has been found to reduce utilization and costs [21, 7577]. Aggressive, angina-targeted clinical trials that also evaluate impact on utilization, and trials using modern psychopharmacological agents, are needed.…”
Section: Discussionmentioning
confidence: 99%